Lecture by Ms. Christine Lagarde at Nazarbayev University - Christine, Lagarde (Nazarbayev University, 2017)
Lecture by Ms. Christine Lagarde, the Managing Director of the International Monetary Fund on the current and prospective global and regional environment, as well as the challenges and opportunities for Kazakhstan and the Caucasus and Central Asia region.
Keywords: Monetary fund; Central Asia; Kazakhstan